Expansion of an Unusual Virtual Memory CD8+ Subpopulation Bearing Vα3.2 TCR in Themis-Deficient Mice - Prasad, Mukul; Wojciech, Lukasz; Brzostek, Joanna; Hu, Jianfang; Chua, Yen Leong; Tung, Desmond Wai Hon; Yap, Jiawei; Rybakin, Vasily; Gascoigne, Nicholas R. J. (Frontiers in Immunology, 2021)
Deletion of the gene for Themis affects T cell selection in the thymus, which would be expected to affect the TCR repertoire. We found an increased proportion of cells expressing Va3.2 (TRAV9N-3) in the peripheral CD8+ T cell population in mice with germline Themis deficiency. Analysis of the TCRa repertoire indicated it was generally reduced in diversity in the absence of Themis, whereas the diversity of sequences using the TRAV9N-3 V-region element was increased. In wild type mice, Va3.2+ cells showed higher CD5, CD6 and CD44 expression than non-Va3-expressing cells, and this was more marked in cells from Themis-deficient mice. This suggested a virtual memory phenotype, as well as a stronger response to self-pMHC. The Va3.2+ cells responded more strongly to IL-15, as well as showing bystander effector capability in a Listeria infection. Thus, the unusually large population of Va3.2+ CD8+ T cells found in the periphery of Themis-deficient mice reflects not only altered thymic selection, but also allowed identification of a subset of bystander-competent cells that are also present in wild-type mice.